Corrigendum Effect of Dietary Supplement of Algae (Spirulina platensis) as an Alternative to Antibiotics on Growth Performance and Health Status of Broiler Chickens - Rubel , Md. Zahir Uddin; Beg, Md. Anwarul Haque; Islam, K.B.M. Saiful; Begum, Maksuda; Patoary, Md. Mahfuj Ullah (International Journal of Poultry Science, 2021)
International Journal of Poultry Science published the above mentioned article in 18(12): 576-584. Now all authors of this manuscript have requested to change the authorship of this article. They want to add Dr. K. B. M. Saiful Islam in the authors list. The reason for this addition is the fact that Dr. K. B. M. Saiful Islam was the co-supervisor of this research project, but his name was mistakenly overlooked by the corresponding author. The new authorship of this article should be considered as follow: Effect of Dietary Supplement of Algae (Spirulina platensis) as an Alternative to Antibiotics on Growth Performance and Health Status of Broiler Chickens 1Md. Zahir Uddin Rubel, 1Md. Anwarul Haque Beg, 2K. B. M. Saiful Islam, 1Maksuda Begum and 3Md. Mahfuj Ullah Patoary 1Department of Poultry Science, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh 2Department of Medicine & Public Health, Faculty of Animal Science & Veterinary Medicine, Sher-e-Bangla Agricultural University, Dhaka-1207, Bangladesh 3Department of Animal Nutrition Genetics and Breeding, Sher-e-Bangla Agricultural University, Dhaka, Bangladesh Citation: Md. Zahir Uddin Rubel, Md. Anwarul Haque Beg, K. B. M. Saiful Islam, Maksuda Begum and Md. Mahfuj Ullah Patoary, 2020. Effect of Dietary Supplement of Algae (Spirulina platensis) as an Alternative to Antibiotics on Growth Performance and Health Status of Broiler Chickens. Int. J. Poult. Sci., 18: 576-584. The original article was published at 10.3923/ijps.2019.576.584